Psychometric properties of the German version of the Psychological Consequences of Screening Questionnaire (PCQ) for liver diseases - Fichtner, Urs A.; Maun, Andy; Farin-Glattacker, Erik (Frontiers in Psychology, 2022)
Background: This study aimed to translate the negative and positive items of the Psychological Consequences Questionnaire (PCQ) into German, to adapt this version to the context of screening for cirrhosis and fibrosis of the liver, and to test its psychometric properties. Methods: The three subscales (physical, emotional, and social) were translated into German using a forward-backward translation method. Furthermore, we adapted the wording to the context of liver diseases. In sum, the PCQ comprises twelve negative items and ten positive items. We tested the acceptability, distribution properties, internal consistency, scale structure, and the convergent validity using an analysis sample of 443 patients who were screened for cirrhosis or fibrosis of the liver. Results: We found low non-response and non-unique answer rates on the PCQ items in general. However, positive items had higher non-response rates. All items showed strong floor effects. McDonald’s Omega was high for both the negative (ω =0.95) and the positive PCQ scale (ω =0.90), as well as for the total PCQ scale (ω=0.86). Confirmatory factor analysis could reproduce the three dimensions that the PCQ intends to measure. However, it suggests not summing up a total PCQ score and instead treat the subscales separately considering a higher order overall construct. Convergent validity with the short form of the Spielberger State-Trait Anxiety Inventory (STAI-Y-6) was acceptable. Conclusions: Overall, our study results report a successful adaptation of the German PCQ with good performance in terms of acceptability, internal consistency, scale structure, and convergent validity. Floor-effects limit the content validity of the PCQ, which needs to be addressed in future research. However, the German version of the PCQ is a useful measurement for both negative and positive screening consequences - even in a non-cancer setting.